Efficacy of rodent pathogen reservoir-targeted topical acaricide treatment strategies to lower the density of host-seeking Ixodes pacificus nymphs in California - Newton Maxwell; Nakano Angie; Summers Shannon; Esquivel Alexander; Swei Andrea (Ticks and Tick-Borne Diseases)
Lyme disease, caused primarily by the bacterium Borrelia burgdorferi sensu stricto (s.s.), is the most prevalent vector-borne disease in the United States. Lyme disease spirochetes are maintained through enzootic cycles of pathogen transmission between vertebrate reservoir hosts and tick vectors. Reservoir host targeted strategies have been examined for their ability to disrupt enzootic transmission cycles of B. burgdoferi s.s. within natural environments in the eastern U.S. However, there are no studies in the western U.S. examining the effect of permethrin- and deltamethrin-based topical acaricides on Ixodes pacificus over consecutive years of treatment. We evaluated rodent reservoir-targeted topical acaricide treatments from 2023 to 2024 in California and examined their impact on larval I. pacificus infesting rodent host species and the density of host-seeking nymphal I. pacificus. Modified bait stations contained topical acaricides to treat dusky-footed woodrats (Neotoma fuscipes), western gray squirrels (Sciurus griseus), and several Peromyscus species throughout the peak of larval and nymphal I. pacificus host-seeking activity between March and May. Topical acaricide treatments including permethrin and deltamethrin were applied on three replicate plots. Our results show that larval I. pacificus burdens decreased by 96 % at acaricide treated plots compared to control plots in 2024. In addition, the density of host-seeking nymphal I. pacificus was 56 % lower at acaricide treated plots compared to control plots in 2024. This suggests that in the western U.S., host-targeted topical acaricide treatments are a highly effective strategy for reducing rodent reservoir-attached ticks as well as the abundance of host-seeking nymphal I. pacificus.